Red Blood Cell Transfusions and Iron Therapy for Patients Presenting with Acute Upper Gastrointestinal Bleeding: A Survey of Canadian Gastroenterologists and Hepatologists. (28th June 2016) - Fortinsky, Kyle J.; Martel, Myriam; Razik, Roshan; Spiegle, Gillian; Gallinger, Zane R.; Grover, Samir C.; Pavenski, Katerina; Weizman, Adam V.; Kwapisz, Lukasz; Mehta, Sangeeta; Gray, Sarah; Barkun, Alan N.
Abstract : Introduction . There is limited data evaluating physician transfusion practices in patients with acute upper gastrointestinal bleeding (UGIB). Methods . A web-based survey was sent to 500 gastroenterologists and hepatologists across Canada. The survey included clinical vignettes where physicians were asked to choose transfusion thresholds. Results . The response rate was 41% (N = 203 ). The reported hemoglobin (Hgb) transfusion trigger differed by up to 50 g/L. Transfusions were more liberal in hemodynamically unstable patients compared to stable patients (mean Hgb of 86.7 g/L versus 71.0 g/L;p < 0.001 ). Many clinicians (24%) reported transfusing a hemodynamically unstable patient at a Hgb threshold of 100 g/L and the majority (57%) are transfusing two units of RBCs as initial management. Patients with coronary artery disease (mean Hgb of 84.0 g/L versus 71.0 g/L;p < 0.01 ) or cirrhosis (mean Hgb of 74.4 g/L versus 71.0 g/L;p < 0.01 ) were transfused more liberally than healthy patients. Fewer than 15% would prescribe iron to patients with UGIB who are anemic upon discharge. Conclusions . The transfusion practices of gastroenterologists in the management of UGIB vary widely and more high-quality evidence is needed to help assess the efficacy and safety of selected transfusion thresholds in varying patients presenting with UGIB.